Spatial and temporal characterization of polarization entanglement - Nomerotski A.; Katramatos D.; Stankus P.; Švihra P. (World Scientific, 2020)
We describe the full temporal and spatial characterization of polarization-entangled photons produced by Spontaneous Parametric Down Conversions using an intensified high-speed optical camera, Tpx3Cam. This novel technique allows for precise determination of Bell inequality parameters and for new characterization methods for the spatial distribution of entangled quantum information. We also discuss a technique to synchronize multiple cameras separated by vast distances, which will be required for a distributed quantum network.
Keywords: Tpx3Cam; entanglement